Re-description of Strandesia sanoamuangae Savatenalinton & Martens, 2010 and description of a new species of Strandesia (Crustacea, Ostracoda) from Grande Terre, New Caledonia - Kisseih, Amanor; Higuti, Janet; Martens, Koen (European Journal of Taxonomy, 2020)
The New Caledonian Archipelago is a hot spot for biodiversity and endemism. Whereas popular groups such as birds and plants are well-studied, invertebrate groups such as ostracods remain ill-known. Here, we re-describe Strandesia sanoamuangae Savatenalinton & Martens, 2010, originally described from Thailand (8000 km away from New Caledonia), and describe Strandesia mehesi sp. nov. Both species are known only from females. Material for the present study was collected from diverse aquatic non-marine habitats from Grande Terre, the main island of New Caledonia. Whereas S. sanoamuangae is seemingly easily identifiable, S. mehesi sp. nov. is part of the Strandesia vinceguerrae/vavrai species cluster in the genus, of which the ‘older’ species (described long ago) often have incomplete and superficial descriptions. Differentiation between the new species and the other members of this species cluster are based on small anatomical details of the valves. The current paper updates the known number of recent freshwater Ostracoda of New Caledonia from 14 to 16 species, although at least five of these species have an uncertain status.